DESAIN PEMBELAJARAN BAHASA ARAB DALAM PERSEKTIF FILSAFAT PENDIDIKAN TRI-KON KI HADJAR DEWANTARA - MUKHOYYAROH (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2023)
Instructional design is a design study conducted in order to transfer knowledge effectively its occur between teacher and student. Instructional design should describe the knowledge to be understood by the students, the learning objectives to be achieved by designing methods, strategies, and instructional media. This can be achieved if educators have views that are in line with their philosophy, including the educational philosophy of Tri-Kon Ki Hadjar Dewanatara, both in terms of the extent to which educators apply the plan in the implementation of learning, so that the indicators set out in the lesson plan are well absorbed by students who can done with cooperative learning, Contextual Teaching Learning. The main objective of learning Arabic is to achieve basic language competencies (listening, speaking, reading, and writing). In order for these basic competencies, the role of educators is very important both as a central and a catalyst in exploring the potential and supporting students to be able to imitate, imitate or duplicate the language skills taught and/or owned by educators both related to the sound system, Nahwu and Sharf, and the lexical system. Educators must be able to design learning activities that are able to